Why second elections in Africa are necessary but not sufficient to consolidate democracy : Zambia and Kenya compared - Marishane, Makabe Boitumelo (Stellenbosch : Stellenbosch University, 2012)
On t.p.: Master of Philosophy in Political Science (Political Management)